2013
DOI: 10.1088/1674-1056/22/5/054204
|View full text |Cite
|
Sign up to set email alerts
|

Emission spectrum of a harmonically trapped Λ-type three-level atom

Abstract: We theoretically investigate the emission spectrum for a Λ-type three-level atom trapped in the node of a standing wave. We show that the atomic center-of-mass motion not only directly affects the peak number, peak position, and peak height in the atomic emission spectrum, but also influences the effects of the cavity field and the atomic initial state on atomic emission spectrum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…[7,15,16] The emission spectrum is a conventional and convenient spectroscopy technology capable of offering valuable information about studied atoms or molecules. [15,[17][18][19][20][21][22][23] Electronically excited CH (A 2 ∆ ) produced by the multi-photon dissociation has been investigated. [4,[24][25][26] Lichtin et al observed electronically excited CH through the photodissociation of CHBr 3 at 266 nm and proposed the mechanism of a three-photon process.…”
Section: Introductionmentioning
confidence: 99%
“…[7,15,16] The emission spectrum is a conventional and convenient spectroscopy technology capable of offering valuable information about studied atoms or molecules. [15,[17][18][19][20][21][22][23] Electronically excited CH (A 2 ∆ ) produced by the multi-photon dissociation has been investigated. [4,[24][25][26] Lichtin et al observed electronically excited CH through the photodissociation of CHBr 3 at 266 nm and proposed the mechanism of a three-photon process.…”
Section: Introductionmentioning
confidence: 99%